Immunohistochemical findings in tubular pattern of adenoid cystic carcinoma affecting the palate: a pathological perspective - Kashyap, Nikita; S., Aravindan; Rakshit, Sudipta; Ray, Jay G. (International Journal of Research in Medical Sciences, 2025)
Adenoid cystic carcinoma (ADCC) is a rare and aggressive epithelial neoplasm of the major and minor salivary glands. It affects 1% of all malignant neoplasms of the oral and maxillofacial region and 22% of all salivary gland malignancies. Most common site affected is palate followed by parotid region, tongue and floor of mouth. It is commonly seen in middle aged population with slight female predilection. Clinically, it is characterized by asymptomatic and slow growth with high propensity for local recurrence and distant metastasis. Diagnosis of ADCC is usually with the help of clinical features, radiographic features and histologic features. It is characterized by the proliferation of ductal (luminal) and myoepithelial cells showing 3 histopathological patterns i. e., cribriform, tubular and solid. We report a case of a 74-year-old male diagnosed with ADCC of the palate, focusing on the clinical presentation, histopathological features, and immunohistochemical profile.